Influence of argon-implantation on conventional and phototransferred thermoluminescence of synthetic quartz. Issue 3 (3rd March 2016) - Nsengiyumva, S.; Chithambo, M. L.; Pichon, L.
ABSTRACT: Conventional and phototransferred thermoluminescence of crystalline synthetic quartz implanted with 70 keV Ar ions at fluences in the range 1 × 10 14 –5 × 10 15 ions/cm 2 is reported. The glow curves, recorded at 5°C/s from beta-irradiated samples of similar mass, show a prominent peak between 100°C and 120°C. The thermoluminescence intensity of all implanted samples was greater than that of the unimplanted one. The increase in sensitivity is attributed to a corresponding increase in the concentration of point defects, as a result of the implantation, which act as electron traps or recombination centres. Kinetic analysis carried out using the peak shape, whole glow-peak and curve-fitting methods produced values of the activation energy, frequency factor and order of kinetics that are generally independent of implantation fluence. This result suggests that implantation did not necessarily affect the nature of the electron traps. With respect to phototransferred thermoluminescence, it was observed that it only appeared in the sample implanted at the highest fluence of 5 × 10 15 ions/cm 2 . This may be so because the concentration of deep traps produced as a result of implantation at low fluence is too low to give rise to phototransferred thermoluminescence. The intensity of the phototransferred thermoluminescence goes through a peak with illumination time. We attribute this behaviour to the relative concentration of holes at recombination centres and phototransferred electrons at shallow traps.